Salinity tolerance of Passiflora tarminiana Coppens & Barney - Hurtado Salazar, Alejandro; Pereira Da Silva, Danielle Fabiola; Ocampo Pérez, John Albeiro; Ceballos Aguirre, Nelson; Bruckner, Claudio Horst (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 11-19).